EKSPLORASI PERSEPSI GURU TERHADAP PEMBELAJARAN MENDALAM (DEEP LEARNING APPROACH) DI MADRASAH IBTIDAIYAH: STUDI DESKRIPTIF KUALITATIF - Wiratama, Rivaldi; Norruzzaini, Annis; Yonisa, Tri (Program Studi PGSD, FKIP, Universitas Mataram, 2025)
This study aims to describe Madrasah Ibtidaiyah teachers’ perceptions of the deep learning approach in classroom instruction. This research employed a descriptive qualitative approach involving 16 teachers from Madrasah Ibtidaiyah Darussalam Awayan as participants. Data were collected through interviews, observations, and documentation, then analyzed using the Miles & Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that teachers generally perceive deep learning positively as an instructional innovation that promotes deeper understanding and improves learning quality. However, many teachers still lack comprehensive understanding of its concepts and implementation due to limited digital literacy, insufficient training, and inadequate technological facilities. These results highlight the need for strengthening teacher competencies and providing sufficient infrastructure to support the effective implementation of deep learning in Madrasah Ibtidaiyah.